Fifteen one-act plays - Shepard, Sam, 1943-2017 (Vintage Books, 2012)
Filled with wry, dark humor, unparalleled imagination, unforgettable characters, and exquisitely crafted storytelling, Sam Shepard's plays have earned him enormous acclaim over the past five decades. In these fifteen one-acts, we see him at his best.